A Study On Evaluating Administration Prevalence And Type Of Cancer In Addicted Individuals In Cancer Patients At Multi-Speciality Hospital (Cuestiones de Fisioterapia, 2025)
Pain is one of the most common symptoms in the cancer population, and cancer-related pain is often treated with opioids. Opioid exposure increases the risk of developing an opioid use disorder (OUD). In addition, a cancer diagnosis can have a significant impact on mental health and wellness, and patients may use substances to cope with psychological distress.